Creeping towards the mutual: lessons from a modest initiative to improve mental health systems capacity in Pacific Island nations. (February 2020) - Hunter, Ernest
Objective: To describe the evolution of the Leadership in Mental Health: Island Nations (LMH:IN) course. Method: Using Transformation Theory the focus on Island Nations mental health capacity building through seven Creating Futures conferences is explored and directions for the future considered. Conclusion: Experience and evaluation identify a set of key factors informing the ongoing development of the LMH:IN course.